O-076 Genomic and morphokinetic blueprint of mosaic embryos is evidence supporting their distinct clinical category. (30th June 2022) - Madjunkov, M; Balakier, H; Abramov, R; Antes, R; Chen, S; Wilkinson, M; Trivodaliev, K; Madjunkova, S; Librach, C
Abstract: Study question: Is there a correlation between blastocyst mosaicism, morphokinetic and morphologic characteristics and can it inform the clinical outcome of mosaic embryo transfers? Summary answer: Mosaic (diploid/aneuploid) embryos have a distinct genetic, morphokinetic and morphologic signature that distinguishes them from euploid and abnormal embryos and supports their unique clinical identity. What is known already: Advances in technologies for preimplantation aneuploidy testing (PGT-A) as the ultimate test for embryo selection has increased the resolution and sensitivity to detect intermediate chromosomal copy number as low as 20%. This has brought to light a biological phenomenon that has created clinical dilemma. Current recommendations support mosaic embryo transfer but with conflicting standpoints ranging from complete dismissal of mosaic embryos to arguing their existence. Time-lapse imaging technologies allow collection of morphokinetic data as a non-invasive assessment tool for embryo development. The aim of this study was to correlate genomic and morphokinetic data with clinical outcomes of mosaic embryos. Study design, size, duration: This is a retrospective cohort study that took place in a single academic IVF centre, where we analysed the results from high resolution PGT-A, morphokinetic, morphologic and cell division features of 4113 embryos cultured in the time lapse imaging incubator (Embryoscope™) from 2016-2021. Associated patient data and transfer outcome of 770 euploid and 147 mosaic embryo transfers were analyzed. Participants/materials, setting, methods: High resolution NGS PGT-A was performed using the Illumina platform and BluGnome and NxClinical for data analysis. Clinically relevant findings were aberrations >10Mb and mosaicism from 25%-75%. Time-lapse imaging was performed with an Embryoscope™. Comparison of clinical, morphological, morphokinetic characteristics of euploid, aneuploid, low-level mosaic (25%-<50% aneuploid cells in trophectoderm biopsy), and high-level mosaics (50% -75%) was done with R-statistical package, Mathlab and SSPS software were used, and p < 0.05 with CI 95% was considered significant. Main results and the role of chance: Aneuploidy was detected in 26.2%, euploidy in 56.7% and diploid-aneuploid mosaicism in 17.1% of embryos included in this study. Compared with euploid embryos, mosaic embryos had significant delays in t2 (27.04±0.35vs.26.4±0.17 h-post-ICSI(hpi), p = 0.0029), which was not correlated with transfer outcome. Embryos with whole chromosome mosaicism (WCM) had longer t2 compared to those with segmental chromosome mosaicism (SCM) (27.29±0.59vs.26.4±0.3hpi, p=0.013). The time to first mitosis was also longer for mosaic vs. euploid embryos (4.57± 0.59vs.3.4±0.25hpi, p=0.000056) and for mosaic embryos with WCM vs SCM embryos (4.64± 0.9 vs 3.5 ±0.5hpi, p=0.04). Mosaic embryos had longer tB &tSB than euploid embryos (110.12±0.69vs.109.13hpi±0.4, p=0.01). Embryos with WCM had longer tB &tSB than those with SCM (111.07±1.09vs.108.7±0.8hpi, p=0.0006). Time to blast was longer for mosaic vs euploid embryos (13.69±0.52vs.12.7±0.4hpi, p=0.0035) and for mosaic WCM vs. SCM embryos (14.3±0.7vs.12.8±0.5hpi, p=0.00084). Both euploid and mosaic embryos that implanted had shorter time to tB&tSB than mosaic embryos that didn't (p = 0.029; p = 0.007 and p = 0.002; p = 0.006 and p = 0.029 respectively); and mosaic embryos that implanted had shorter time to first mitosis than euploid embryos that didn't (p = 0.00228). High level mosaic embryos had significantly more multinucleation at 2-cell stage (MN2) vs. euploid (p = 0.04, OD1.58-95%CI[1.01-2.45]), aneuploid (p = 0.02, OD1.7-95%CI[1.08-2.8]), as well as MN at 4-cell stage (euploid-p=0.0007, OD2.6-95CI1.4-4.7] and aneuploid-p=0.039, OD1.8-95CI1.02-3.4]). Limitations, reasons for caution: Although this is the largest study to date that evaluated genomic, morphokinetic and outcome data of mosaic transfers, the numbers are still low to analyze the impact of specific chromosomal aberrations on morphokinetics and pregnancy outcome. The retrospective nature and cohort design limited the generalizability of our results. Wider implications of the findings: Mosaic embryos have significant developmental potential and result in birth of healthy babies. Our study reveals the genomic interconnection of genomic and morphokinetic features of mosaic embryos and provides further evidence that mosaic embryos are a distinct category that requires specific clinical attention. Trial registration number: Not applicable